Perancangan Sistem Informasi Pemasaran Kakao Berbasis Web UD. Harta Sari - Putra S, Putu Yoga Pratama; Satriawan, I Ketut; Budisanjaya, I Putu Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Marketing information systems are designed to make it easier for companies to promote their products. This study purpose is to design MIS of Harta Sari cocoa company and to find out what key factors are needed in designing MIS. Research on the design of MIS uses tools such as CMS, MySQL to generate MIS. Web quality analysis is done using blackbox method to test web functionality and user acceptance tests used to determine the level of website acceptance generated. The results of testing the blackbox method showed the website is functioning normally as it should, the key factors in the designing MIS of Harta Sari cocoa company are design, content and usability. The results of the questionnaire assessment using the user acceptance test method showed the results for the design factor were very good with an average percentage of 80.44%, for the content factor it was quite complete with an average percentage of 77.07% and for the usability factor it was sufficient easy to operate with an average percentage of 71.87%. Keywords: marketing, management information system, cocoa company.